A New Proposal of Criteria for the Future Remnant Liver Volume in Older Patients Undergoing Major Hepatectomy for Biliary Tract Cancer. Issue 2 (February 2018) - Watanabe, Yoshihiro; Kuboki, Satoshi; Shimizu, Hiroaki; Ohtsuka, Masayuki; Yoshitomi, Hideyuki; Furukawa, Katsunori; Miyazaki, Masaru
Abstract : Objective: To evaluate whether advanced age increases the risk of severe complications after major hepatectomy with bile duct resection (BDR) in patients with biliary tract cancer, and to establish new criteria for the percentage of the future remnant liver volume (%FLV) in older patients undergoing this operation. Background: Advanced age is reported to inhibit liver regeneration and suppress immune function; however, little is known about the risk of aging in high-stress surgery, such as biliary tract surgery. Methods: Consecutive patients who underwent major hepatectomy with BDR between 2000 and 2013 were retrospectively reviewed. Severe postoperative complications were defined as Clavien-Dindo grade ≥IV. Results: In 225 patients undergoing major hepatectomy with BDR, advanced age was significantly correlated with the incidence of severe postoperative complications, with cut-off value of 69 years. In comparing postoperative complications, the incidences of hyperbilirubinemia, liver failure, respiratory failure, sepsis, severe complications, and operation-related death were more frequent in the older group. Moreover, advanced age (≥69 years) was an independent risk factor associated with severe complications after major hepatectomy with BDR. Delayed liver regeneration was the reason for the age-related risks. The incidence of severe postoperative complications in older patients was significantly decreased if %FLV was set at ≥45%. Conclusions: Advanced age is a strong independent risk factor for severe complications after major hepatectomy with BDR. To decrease the risk of advanced age, the minimum limit of %FLV for this operation should be set at ≥45% in patients aged ≥69 years.